2012
DOI: 10.1681/asn.2011050442
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injury Accelerates Cystogenesis via Pathways Modulated by Heme Oxygenase and Complement

Abstract: AKI accelerates cystogenesis. Because cystogenic mutations induce strong transcriptional responses similar to those seen after AKI, these responses may accelerate the progression of cystic renal disease. Here, we modulated the severity of the AKI-like response in Cys1 cpk/cpk mice, a model that mimics autosomal recessive polycystic kidney disease. Specifically, we induced or inhibited activity of the renoprotective enzyme heme oxygenase (HO) and determined the effects on renal cystogenesis. We found that induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…These data are consistent with our earlier observation of a cystic disease progression-inhibiting effect of genetically induced C3 deficiency on autosomal recessive polycystic kidney disease (ARPKD) in the Cys1 cpk mouse model [2], and with the known association of C3-activity altering gene polymorphisms with renal function decline amongst patients with ADPKD [3]. Consistent with the opinion expressed by Su et al [1], we attributed the renal cystogenesis-promoting effects of complement to its intrarenal dysregulation [2,4]. We supported this hypothesis by documenting transcriptional dysregulation for genes encoding multiple complement proteins within kidneys with rapidly vs slowly progressing cystic disease [4].…”
supporting
confidence: 93%
“…These data are consistent with our earlier observation of a cystic disease progression-inhibiting effect of genetically induced C3 deficiency on autosomal recessive polycystic kidney disease (ARPKD) in the Cys1 cpk mouse model [2], and with the known association of C3-activity altering gene polymorphisms with renal function decline amongst patients with ADPKD [3]. Consistent with the opinion expressed by Su et al [1], we attributed the renal cystogenesis-promoting effects of complement to its intrarenal dysregulation [2,4]. We supported this hypothesis by documenting transcriptional dysregulation for genes encoding multiple complement proteins within kidneys with rapidly vs slowly progressing cystic disease [4].…”
supporting
confidence: 93%
“…Numerous models have been proposed to account for the development of cysts. [20][21][22] Zheleznova et al 23 suggested that epidermal growth factor receptor-mediated interactions are key elements in renal tubular cell proliferation, not only in the normal kidney, but also under conditions of cyst formation and enlargement. Activation of the intrinsic kinase domain results in phosphorylation of specific tyrosine residues, which in turn leads to the activation of intracellular signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of cystic kidney disease there is increased expression of complement genes in cyst epithelium, particularly C3, and also evidence of complement activation [57,58] . To investigate a role for complement in cystogenesis Cys1 cpk/cpk polycystic kidney disease mice were crossed with C3 deficient mice which lack the main effector functions of complement [58] . Mice deficient in C3 deve loped fewer cysts and had reduced renal volume, suggesting that complement, possibly by modifying inflammation, has a role in cyst development.…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%
“…It is evident that inflammatory and fibrotic changes occur in renal tissue surrounding the cyst and this may in part be responsible for the loss of renal function that occurs. In mouse models of cystic kidney disease there is increased expression of complement genes in cyst epithelium, particularly C3, and also evidence of complement activation [57,58] . To investigate a role for complement in cystogenesis Cys1 cpk/cpk polycystic kidney disease mice were crossed with C3 deficient mice which lack the main effector functions of complement [58] .…”
Section: Polycystic Kidney Diseasementioning
confidence: 99%